Contribution of Magnetic Resonance Imaging in Determining Lumpectomy Cavity in Breast Radiotherapy - Demircioglu, Ozlem; Tepetam, Huseyin; Eren, Ayfer A.; Ozgen, Zerrin; Demircioglu, Fatih; Aribal, Erkin (Current Medical Imaging, 2020)
Background: Accurate localization of the lumpectomy cavity is important for breast cancer radiotherapy after breast-conserving surgery (BCS), but the LC localization based on CT is often difficult to delineate accurately. The study aimed to compare CT-defined LC planning to MRI-defined findings in the supine position for higher soft-tissue resolution of MRI. Methods: Fifty-nine breast cancer patients underwent radiotherapy CT planning in supine position followed by MR imaging on the same day. LC was contoured by the radiologist and radiation oncologist together by CT and MRI separately. T2 weighted MR images and tomography findings were combined and the LC volume, mean diameter and the longest axis length were measured after contouring. Subsequently, patients were divided into two groups according to seroma in LC and the above-mentioned parameters were compared. Results: We did not find any statistically significant difference in the LC volume, mean diameter and length at the longest axis between CT and MRI but based on the presence or absence of seroma, statistically significant differences were found in the LC volumes and the length at the longest axis of LC volumes. Conclusion: We believe that the supine MRI in the same position with CT will be more effective for radiotherapy planning, particularly in patients without a seroma in the surgical cavity.
Keywords: MRI